Kemampuan Pemecahan Masalah Fisika melalui Pembelajaran Berbasis Proyek Terintegrasi Ethnophysics: Sebuah Studi Pendahuluan - Sri Wahyu Widyaningsih; Dedi Kuswandi; Punaji Setyosari; Saida Ulfa; Irfan Yusuf (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2026)
This study aims to analyze students' physics problem-solving skills through project-based learning integrated with ethnophysics. The research employed a quantitative, quasi-experimental design with a one-group pretest–posttest. The participants consisted of 52 eleventh-grade science students at SMAN 2 Manokwari. The instrument used was a physics problem-solving skills test. Data were analyzed using descriptive statistics and a paired-samples t-test. The results showed that students' initial problem-solving skills were in the very low category. After implementing an ethnophysics-integrated project-based learning approach, changes in students' abilities were observed, as indicated by shifts in the distribution of ability levels. The paired-samples t-test results showed a p-value of 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. Thus, an ethnophysics-integrated project-based learning approach has the potential to support the development of students' physics problem-solving skills and to serve as a contextual and innovative alternative to learning